Psychological factors associated with COVID-19 related anxiety and depression in young adults during the COVID-19 pandemic. - Ye Eun Lee; Jun Ho Seo; Shin Tae Kim; Sumoa Jeon; Chun Il Park; Se Joo Kim; Jee In Kang (PLoS ONE, 2023)
Background The coronavirus disease 2019 (COVID-19) pandemic and the corresponding lockdown have drastically changed our lives and led to high psychological distress and mental health problems. This study examined whether psychological factors such as loneliness, perfectionism, and health anxiety are associated with COVID-19 related anxiety and depression during the pandemic in young Korean adults, after controlling for various socio-demographic factors and early life stress. Methods A total of 189 participants (58.2% women) completed a cross-sectional online survey including the Fear of COVID-19 Scale, Center for Epidemiologic Studies Depression Scale, 3-item Revised UCLA Loneliness Scale, Frost Multidimensional Perfectionism Scale, and Whiteley Index-6. Hierarchical linear regression analyses with three blocks were employed to identify the factors that contributed to COVID-19 related anxiety and depressive symptoms. Results Hierarchical regression analyses showed that higher health anxiety was significantly associated with more severe COVID-19 related anxiety (standardized regression coefficient, β = 0.599, p < 0.001). Additionally, higher levels of loneliness (β = 0.482, p < 0.001), perfectionism (β = 0.124, p = 0.035), and health anxiety (β = 0.228, p < 0.001) were significantly associated with higher depression scores. The three psychological factors explained 32.8% of the total variance in depressive symptom scores, after taking all covariates into account. Conclusion The results showed that health anxiety was a risk factor for both COVID-19 related anxiety and depression in young adults. Loneliness was the strongest predictor of depressive symptoms during the COVID-19 pandemic. These findings highlight the importance of identifying vulnerable individuals and encouraging psychological counselling and social connections to reduce the burden of psychiatric disorders during the pandemic.